Podometry and mineral content in hooves of Campeiro horses Podometrie und Mineralgehalt in Hufen von Campeiro-Pferden - de Souza A.F.* (2021)
© 2021 Hippiatrika Verlagsgesellschaf. All rights reserved.The Campeiro horses descend from animals brought into southern Brazil by Spaniards between the sixteenth and seventeenth centuries. They have shown adaptations to local climatic conditions, types of feeding, management, and selection models to which they have been exposed over the years. This study aims to investigate the characteristics of hooves of the Campeiro horse by means of morphometry and measurement of the contents of some minerals and propose an approach to assess the balance of the palmar/plantar region of the hooves. Hoof morphometry data from the fore and hind hooves of 50 horses were recorded. The mediolateral balance of hooves was assessed by the symmetry of heels, assessing their vertical, linear, and angular metrics. Contents of Ca, Mg, Cu, Fe, and Zn were measured by atomic absorption spectrophotometry, while K and Na levels were measured by atomic emission in sole, wall and frog. Forelimbs showed longer and wider hooves and longer frog. Toe angle was higher in hindlimbs, while the ratio body mass/hoof-ground contact area was similar between the limbs. High frequency of frog contraction (40.4%), angular imbalance of heels (differences greater than five degrees between lateral and medial heels) (30.3%) and underrun heels (82.7%) was observed. Regardless of pigmentation, hoof contents of Cu, Fe, and Zn were higher in the wall, while K, Ca, and Mg levels were greater in the frog. Pigmented hooves (dark) had higher levels of Fe in the wall and sole and higher levels of K in the sole and frog compared to the non-pigmented hooves (light). We can infer that indirect measures of hoof height and palmar/plantar region were adequate. Furthermore, differences in the content of some minerals between dark and light hooves did not reflect on differences in quality.